In Vivo Kinetics of Mesenchymal Stem Cells Transplanted into the Knee Joint in a Rat Model Using a Novel Magnetic Method of Localization. Issue 5 (12th May 2015) - Ikuta, Yasunari; Kamei, Naosuke; Ishikawa, Masakazu; Adachi, Nobuo; Ochi, Mitsuo
Abstract: We have developed a magnetic system for targeting cells in minimally invasive cell transplantation. Magnetically labeled MSCs (m‐MSCs) with nanoscale iron particles can be guided into the desired region by magnetic force from an extracorporeal device. We reported that magnetic targeting of m‐MSCs enhances cartilage repair in a mini‐pig model. However, the detailed kinetics of these magnetically targeted m‐MSCs remain unknown. For clinical use, this aspect should be clarified from a safety standpoint. We therefore investigated the spatial and temporal distribution of the fluorescently‐labeled m‐MSCs transplanted into the knee joint using in vivo fluorescence combined with three‐dimensional computed tomographic imaging in a rat model. Although the intraarticularly injected m‐MSCs were spread throughout the joint cavity in the absence of magnetic force, the magnetic force caused the injected m‐MSCs to accumulate around the chondral lesion. Further examinations including ex vivo imaging, histological assessments and reverse transcription polymerase chain reaction revealed that transplanted MSCs were not present in any major organs after intraarticular administration, regardless of magnetic targeting. Our data suggest that m‐MSCs can be accumulated efficiently into a chondral lesion using our magnetic targeting system, while none of the intraarticularly transplanted MSCs migrate to other major organs.